Avaliação da sustentabilidade urbana com base nas diretrizes de ruas completas e objetivos de desenvolvimento sustentável - Rodighero, Gabriel (2021)
Together, the population increase and migration to the big cities resulted in problems in the big urban centers. The world population, in the year 2019, reached more than 7.7 billion people, with more than half living in urban areas. This has increasingly shown the deficient infrastructure and the lack of studies on the subject, since the debates on sustainable development only started in 1972. . In addition, to reconcile the several items that make up sustainable urban development is a hard work. This research aimed to propose an index to assess the development of local data based on the Complete Streets guidelines and the Sustainable Development Goals of the United Nations. Through a questionnaire with experts and statistical analysis of the responses, five objectives were selected, with SDG 11 (Sustainable Cities and Communities) showing the greatest association with the ideas proposed in the concept of Complete Streets. To select the main domains that made up the index, specialists, the general population and the government were interviewed to determine possible divergences regarding the importance of the items listed. The index elaborated is composed of 21 domains, divided into 49 indicators and consists of an easy-to-apply tool, aiming to understand urban sustainability in all spheres. Its subsequent application and discussion of the results in the proposed location demonstrated that the implementation of awareness campaigns is very important, as the population has different ideas from the ideal advocated by the main studies in the area. Finally, through data collected and obtained from the responsible agencies, it has been that the assessed stretch of the city of Passo Fundo is deficient in several areas of this study, such as the implementation of policies to reduce private vehicles, cycling infrastructure and urban public transport and the amount of green area per inhabitant.